Improvement of Pancreatic Steatosis and Indices of Insulin Resistance After Metabolic Surgery - Salman, Ahmed Abdallah; Salman, Mohamed Abdalla; Said, Mostafa; El Sherbiny, Mohammad; Elkassar, Hesham; Hassan, Mohamed Badr; Marwan, Ahmed; Morad, Mohamed Abdelkader; Ashoush, Omar; Labib, Safa; Aon, Mohamed H.; Awad, Abeer; et al. (Frontiers in Medicine, 2022)
Purpose Obesity is associated with fat accumulation in ectopic sites such as the pancreas, the so-called pancreatic steatosis (PS). Bariatric surgery has been shown to be associated with reducing pancreatic fat. This study investigated the effect of laparoscopic sleeve gastrectomy (LSG) on pancreatic volume and its fat content and glucose homeostasis. Methods The study enrolled 54 patients subjected to LSG. Metabolic variables and pancreatic exocrine function were assessed immediately before surgery and 12 months after. MRI of the abdomen was performed to measure pancreatic fat content and its total volume and visceral adipose tissue (VAT). Results Surgery resulted in a significant reduction in body weight and BMI. HbA1c, fasting insulin, C-peptide levels, HOMA-IR, and Hs-CRP levels decreased significantly. Surgery resulted in significant improvement in lipid profile except for HDL-cholesterol and liver function tests. Total VAT volume decreased significantly. Total pancreas volume decreased by a mean of 9.0 cm3 (95% CI: 6.6–11.3). The median change of pancreatic fat was −26.1% (range: −55.6 to 58.3%). Pancreatic lipase decreased significantly (P < 0.001). There was a positive correlation between the percentage of total weight loss and decrease in pancreatic fat volume (r = 0.295, P = 0.030). Conclusion Weight loss after LSG is associated with a reduction of total VAT volume, total pancreatic volume, and pancreatic fat content. These changes are associated with improved glucose homeostasis, reduced systemic inflammation, and decreased pancreatic lipase secretion.